Teachers’ talent beliefs in the domain of verbal giftedness—the questionnaire - Rogl, Silke; Hamader, Kathrin Claudia; Klug, Julia (Frontiers in Education, 2025)
IntroductionTeachers’ beliefs about their students’ giftedness and talent are relevant to teaching quality and educational processes. Teachers’ beliefs about giftedness have been investigated in mathematics. In our research, we extended this approach to verbal giftedness to examine whether teachers’ beliefs concerning verbal giftedness can be assessed in a manner similar to their talent beliefs in mathematics.MethodsTo this end, we developed and tested a questionnaire to elicit participants’ verbal talent beliefs through a quantitative survey of 207 student teachers.ResultsA six-factor model, similar to the mathematics talent beliefs model, showed good model fit. In the structural model, verbal talent beliefs predicted both student teachers’ growth mindsets and self-efficacy.DiscussionThis questionnaire on verbal talent beliefs can be used in future research projects to optimize teacher education, to better understand educational processes, and facilitate the participation of all students, including gifted students.